(untitled) (Medical Forum Monthly, 2026)
Purpose: The success of a pulpectomy in primary teeth depends on the material used in the root canal filling process. This material needs to have a complex anatomy and a small volume of empty space. It also needs to be resorbed at a similar rate to the root. This article aims to highlight the latest developments in primary teeth root canal fillings and their materials and the role of their rheological properties. Methods: This is a narrative review of lab, in vitro, and clinical studies on four different types of root canal fillings: zinc oxide-eugenol, calcium hydroxide paste, iodoform paste, and bioactive and bioceramic materials from March 2025 till August 2025. Results: The most important factor is the material’s apparent viscosity and flow under shear stress. Thixotropy is also a critical factor in root canal fillings. The yield stress is a measure of the material’s resistance to flow when there is a force applied. The time dependency is a measure of the material’s flow when time is a factor. Conclusion: The success of a root canal filling is dependent on the three-dimensional material used. Rheological properties play a critical role in the success of a root canal filling in primary teeth.